1998
DOI: 10.1007/s004410051054
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal differentiation is accompanied by NSP-C expression

Abstract: Neuroendocrine-specific protein (NSP) reticulons are expressed in neural and neuroendocrine tissues and cell cultures derived therefrom, while most other cell types lack NSP-reticulons. Three major subtypes have been identified so far, designated NSP-A, NSP-B, and NSP-C. We have investigated the correlation between the degree of neuronal differentiation, determined by morphological and biochemical criteria, and NSP-reticulon subtype expression. For this purpose, several human neuroblastoma cell lines, exhibiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 15 publications
1
31
0
Order By: Relevance
“…[23][24][25] RTN-1C represents the smallest variant of the reticulon 1 gene 26 and it is specifically expressed by neurons and cells of neuroendocrine tissue. 27 In our study, we used the previously developed tetracycline-inducible SH-SY5Y RTN-1C human neuroblastoma model 23 consisting of a SH-SY5Y cell line stably expressing tetracycline-inducible RTN-1C (SH-SY5Y RTN-1C ) and a control cell line expressing the regulator vector alone (SH-SY5Y Tet12 ) (Figure 1a). After addition of doxycycline, a tetracycline derivative, SH-SY5Y RTN-1C cells overexpress RTN-1C within hours, reaching a peak around 6 h that remains constant for several days (Figure 1b).…”
Section: Resultsmentioning
confidence: 99%
“…[23][24][25] RTN-1C represents the smallest variant of the reticulon 1 gene 26 and it is specifically expressed by neurons and cells of neuroendocrine tissue. 27 In our study, we used the previously developed tetracycline-inducible SH-SY5Y RTN-1C human neuroblastoma model 23 consisting of a SH-SY5Y cell line stably expressing tetracycline-inducible RTN-1C (SH-SY5Y RTN-1C ) and a control cell line expressing the regulator vector alone (SH-SY5Y Tet12 ) (Figure 1a). After addition of doxycycline, a tetracycline derivative, SH-SY5Y RTN-1C cells overexpress RTN-1C within hours, reaching a peak around 6 h that remains constant for several days (Figure 1b).…”
Section: Resultsmentioning
confidence: 99%
“…Hens and coworkers (40) recently showed that highly differentiated neuronal cell lines expressed NSP-C to a higher extent than cell lines showing less neuronal differentiation. Moreover, induction of neuronal differentiation in undifferentiated pheochromocytoma PC12 cells induced a strong increase in NSP-C expression.…”
Section: Discussionmentioning
confidence: 99%
“…Also known as neural cell adhesion molecule (NCAM) [31] Oct-4 Expressed by undifferentiated embryonic stem cells and embryonic germ cells [32] Nestin Stem/progenitor cells, glioma cells, and tumor endothelial cells in the mammalian CNS [33] Class III β-tubulin Also referred to as TuJ1. Expressed in central and peripheral nervous systems (CNS and PNS) where it is prominently expressed during fetal and postnatal development.…”
Section: Cd56mentioning
confidence: 99%